Effect of PPARGC1A on the development and metabolism of early rabbit embryos in vitro. Issue 11 (18th September 2019) - Zhang, Guo‐Min; Guo, Yi‐Xuan; Deng, Ming‐Tian; Wan, Yong‐Jie; Deng, Kai‐Ping; Xiao, Shen‐Hua; Meng, Fan‐Xing; Wang, Feng; Lei, Zhi‐Hai
Abstract: Peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha ( PPARGC1A ) is a central regulator of mitochondrial biogenesis and metabolism, and its expression is closely related to embryo development. To gain insights into the possible mechanisms of PPARGC1A during early embryogenesis, the development potential, mitochondrial biogenesis, and the culture medium metabolomics of embryos were evaluated when PPARGC1A overexpressed or suppressed in rabbit zygotes. Results showed that different PPARGC1A levels in rabbit zygotes could affect blastocyst percentage, and the expressions of mitochondrial biogenesis and metabolic‐related genes, as well as the glutathione and adenosine triphosphate levels during early embryo development. In addition, compared with the controls, 12 and 10 different metabolites involved in carbohydrate, amino acid, and fatty acid metabolism were screened in the 5 day's spent culture medium of PPARGC1A overexpressed and suppressed embryos by gas chromatography–mass spectrometer, respectively. Consistent with these metabolite changes, the transcriptions of genes encoding glucose transporters and fatty acid biosynthetic proteins in the embryos from different groups were regulated by PPARGC1A during rabbit embryo development. Taken together, these data provide evidence that PPARGC1A may regulate early rabbit embryo development through mitochondrial biogenesis and metabolism. Abstract : Proliferator‐activated receptor gamma coactivator 1‐alpha ( PPARGC1A ) improved rabbit embryo development; increased mitochondrial biogenesis in PPARGC1A overexpressed embryos; PPARGC1A overexpressed embryos exhibited high glucose consumption and glutamine uptake.